Abnormal intrahemispheric and interhemispheric dynamic functional connectivity density in male alcohol use disorder - Mei, Bohui; Wei, Yarui; Ma, Longyao; Tao, Qiuying; Dang, Jinghan; Sun, Jieping; Zhang, Mengzhe; Zhang, Yong; Cheng, Jingliang (Frontiers in Psychiatry, 2025)
BackgroundPrevious studies have demonstrated abnormal static intrahemispheric and interhemispheric functional connectivity between different brain regions in patients with alcohol use disorder (AUD). However, brain activity is highly dynamic.MethodsTo address this, we analyzed the dynamic changes in intrahemispheric and interhemispheric connectivity patterns from 55 AUD patients and 32 healthy controls. The whole-brain functional connectivity was decomposed into ipsilateral and contralateral components, and the voxel-wise intrahemispheric and interhemispheric dynamic functional connectivity density (dFCD) was calculated using a sliding window analysis. At the same time, the relationship between dFCD values in abnormal brain regions and clinical variables was conducted.ResultsOur findings revealed that, compared to the HCs, AUD patients exhibited abnormal global, interhemispheric and intrahemispheric dFCD in the caudate, insula, parietal lobe, and occipital lobe. Furthermore, the dFCD values of these abnormal brain regions correlated with the average alcohol consumption and the severity of alcohol addiction in the AUD group.ConclusionsThe results indicate that brain regions associated with the salience network, default mode network, and visual network exhibited intrahemispheric and interhemispheric abnormal functional connectivity. This study underscores that dynamic metrics can provide overlapping or complementary information alongside static metrics, contributing to a more comprehensive understanding of neural activity in AUD.